Controllable intein splicing and N-terminal cleavage at mesophilic temperatures - McNeal, Taylor A.; Weinberger, Joel; Liman, Geraldy L. S.; Ariagno, Tia M.; Wood, David W.; Santangelo, Thomas J.; Lennon, Christopher W. (Frontiers in Bioengineering and Biotechnology, 2025)
Inteins (intervening proteins) interrupt host proteins and are removed through a protein splicing reaction that ligates adjacent N- and C-exteins. The ability of inteins to specifically rearrange peptide bonds has proven exceptionally useful in protein engineering, thus, methods to control intein activity are of considerable interest. One particularly useful application of inteins is for the removal of an affinity tag following purification of a target protein through N-terminal cleavage (NTC). Typically, extended incubation at high temperature (greater than 50°C) or with an external nucleophile (e.g., dithiothreitol) is required to drive NTC, conditions that compromise the folding of many target proteins. Here, we characterize a variant of the Thermococcus kodakarensis RadA intein that can perform NTC at moderate temperatures in the absence of an external nucleophile. While we find that while NTC is largely inhibited during expression in Escherichia coli at 15°C, rapid and efficient NTC can be activated 37°C. Our results provide an alternative intein-based system – one that does not require either an external nucleophile or prolonged incubation at high temperature to stimulate NTC – that controls intein activity within a temperature range amenable to most mesophilic experimental organisms.